2015
DOI: 10.3892/or.2015.3958
|View full text |Cite
|
Sign up to set email alerts
|

RNF8 plays an important role in the radioresistance of human nasopharyngeal cancer cells in vitro

Abstract: Tumor residue or recurrence is common after radiation therapy for nasopharyngeal cancer (NPC) since the tumor cells can repair irradiation-induced DNA damage. The ubiquitination cascade mediates the assembly of repair and signaling proteins at sites of DNA double-strand breaks (DSBs). Ring finger protein 8 (RNF8) is an E3 ubiquitin ligase that triggers ubiquitination at the site of DSBs. The present study aimed to identify whether and how RNF8 small interfering RNA (siRNA) treatment enhances the radiosensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Furthermore, the expression of checkpoint proteins Chk1 and Chk2 and DNA damage proteins ATM and Nbs1 was reduced in RNF8 knockdown cells with irradiation treatment, which impeded DNA repair function. The repair capacity of irradiation-induced DNA damage is a common factor for NPC recurrence after radiation therapy [78]. These results suggest that RNF8 is required in NPC cells for resistance to radiation therapy.…”
Section: Tumorigenesis and Cancer Progressionmentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, the expression of checkpoint proteins Chk1 and Chk2 and DNA damage proteins ATM and Nbs1 was reduced in RNF8 knockdown cells with irradiation treatment, which impeded DNA repair function. The repair capacity of irradiation-induced DNA damage is a common factor for NPC recurrence after radiation therapy [78]. These results suggest that RNF8 is required in NPC cells for resistance to radiation therapy.…”
Section: Tumorigenesis and Cancer Progressionmentioning
confidence: 83%
“…In contrast, the DNA damage response function of RNF8 in certain cancers is involved in radiation therapy resistance [78,79]. When the telomere was already uncapped by deletion of TRF2, the E3 ligase activity of RNF8 in promoting H2A ubiquitination helped to induce C-NHEJ and further caused genomic instability [46].…”
Section: Conclusion Remarks and Perspectivesmentioning
confidence: 99%
“…However, a previous study has revealed that decreased RNF8 expression can significantly improve radiotherapy sensitivity in nasopharyngeal cancer, while inhibiting cell proliferation and increasing apoptosis (31). In breast cancer MCF-7 cells, overexpression of RNF8 can significantly increase epithelial-mesenchymal transition and it mainly promotes phosphorylation of GSK3β, further inhibiting its activity (10).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, an increase in phosphorylation of β-catenin has been observed in RNF8-overexpressing cells (10). Furthermore, in the treatment of breast cancer using tamoxifen to block ERα, tamoxifen exerts anticancer effects mainly by blocking the ERα signaling pathway (31), but a previous study has revealed that RNF8 can activate the ERα signaling pathway and thus promote tumor cell proliferation (8). The aforementioned studies did not focus on p53 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of RNF8 retains Ku80 on DNA and impairs NHEJ e ciency [36]. Recent study found that RNF8 facilities doxorubicin resistance in cancer stem cells [37]and radiation resistance in nasopharyngeal cancer, bladder cancer [38,39]. These studies prompt us to investigate the role of RNF8 in NHEJ in EC.…”
Section: Discussionmentioning
confidence: 99%